If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 69 + -4x = 14x + 21 Reorder the terms: 69 + -4x = 21 + 14x Solving 69 + -4x = 21 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 69 + -4x + -14x = 21 + 14x + -14x Combine like terms: -4x + -14x = -18x 69 + -18x = 21 + 14x + -14x Combine like terms: 14x + -14x = 0 69 + -18x = 21 + 0 69 + -18x = 21 Add '-69' to each side of the equation. 69 + -69 + -18x = 21 + -69 Combine like terms: 69 + -69 = 0 0 + -18x = 21 + -69 -18x = 21 + -69 Combine like terms: 21 + -69 = -48 -18x = -48 Divide each side by '-18'. x = 2.666666667 Simplifying x = 2.666666667
| 9x+x+4=180 | | 4w+8=6(w-1)-2w | | 2(5-3d)=16-7d | | 6(v+3)=-5v-15 | | 4x-140=2x+60 | | 4y-20=7(y-5) | | 8g+12-6g=-8 | | 9-(4p-3)+p=36 | | (n-9)*9=90 | | n-9*9=90 | | 2x=x-36 | | 4+6x+12-3x= | | 8a-(5a+1)=8-2(a-3) | | 9(y-5)=7y-37 | | 16x^2-4x-4=0 | | (6a^2+5a)(-12a+2)=0 | | N-14=15 | | 13589989+259003-145690= | | 12x-56=63x | | 90=x+x*0.25 | | 2.x-3=9 | | 3x-1=-17 | | (4x-3)(x+1)=0 | | 5x-50=x+90 | | 149-3x=24x+17 | | 4(r-7)+1=5(r+3)-25 | | 5(3+x)-4(x+1)=2 | | 6y-4=35+6y | | 2(x+3)+4(x-1)=1 | | 6(q-2)=9 | | 22x+6=-90-10x | | 7+7x=14x-14 |